Leptospirosis presenting as acute pancreatitis and cholecystitis. - Dalamaga, Maria; Chavelas, Charilaos; Kostoula, Angeliki; Matekovits, Helen; Karmaniolas, Konstantinos; Liatis, Stavros; Migdalis, Ilias (J Med, 2004)
We report a rare case of a 21-year-old man with leptospirosis mimicking acute pancreatitis and cholecystitis. This case report aims at pointing out the need of taking into consideration the possibility of leptospirosis in patients with an influenza-like syndrome, headache accompanied by acute abdominal pain and a suspicious exposure in order to prevent unnecessary surgical interventions.
Keywords: Adult; Cholecystitis; Diagnosis, Differential; Humans; Leptospira interrogans; Leptospirosis; Male; Pancreatitis